2016
DOI: 10.1002/advs.201600331
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of Interfacial Energetics in Organic Multiheterojunctions

Abstract: Efficient charge generation via exciton dissociation in organic bulk heterojunctions necessitates donor–acceptor interfaces, e.g., between a conjugated polymer and a fullerene derivative. Furthermore, aggregation and corresponding structural order of polymer and fullerene domains result in energetic relaxations of molecular energy levels toward smaller energy gaps as compared to the situation for amorphous phases existing in homogeneously intermixed polymer:fullerene blends. Here it is shown that these molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 83 publications
(171 reference statements)
2
40
0
Order By: Relevance
“…In the case of a ternary blend of polymer:fullerene solar cells studied by Kästner et al, a controlled ratio of semicrystalline and amorphous polymers was used to vary the D–A interface from disordered–disordered, over disordered–ordered, up to ordered–ordered ( Figure 3 a). By including these intercalated phases (for example, amorphous PCBM and amorphous polymer molecularly intermixed with PCBM) and probing the interfaces via electroluminescence and photoluminescence, the authors concluded that six unique CT transitions were present in this system, with the highest energy CT state forming between the disordered–disordered interface and the lowest energy CT state occurring at the ordered–ordered interface …”
Section: Experimental Evidence For Ct State Shifts Under Different Momentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of a ternary blend of polymer:fullerene solar cells studied by Kästner et al, a controlled ratio of semicrystalline and amorphous polymers was used to vary the D–A interface from disordered–disordered, over disordered–ordered, up to ordered–ordered ( Figure 3 a). By including these intercalated phases (for example, amorphous PCBM and amorphous polymer molecularly intermixed with PCBM) and probing the interfaces via electroluminescence and photoluminescence, the authors concluded that six unique CT transitions were present in this system, with the highest energy CT state forming between the disordered–disordered interface and the lowest energy CT state occurring at the ordered–ordered interface …”
Section: Experimental Evidence For Ct State Shifts Under Different Momentioning
confidence: 99%
“…a) Schematics of several morphological configurations of donor/acceptor interfaces with varying degrees of order and their associated energy‐level diagrams of resulting CT states reflecting the expected changes in CT state energy. Reproduced with permission . Copyright 2016, WILEY‐VCH Verlag GmbH & Co. KGaA.…”
Section: Experimental Evidence For Ct State Shifts Under Different Momentioning
confidence: 99%
See 1 more Smart Citation
“…This can be, connected to an improved vertical alignment of the materials within the photoactive layer, as already indicated by the increased parallel resistance, leading to a more efficient injection and transport of holes and electrons from the anode and cathode, respectively, towards the materials interface at the heterojunction. It is furthermore interesting to note that the peak energy of the CTtransition seems to be reduced (from ~920 to ~ 945 nm) for the methanol modified blend, which confirms a higher order in the transport states [65], respectively the access to them during charge injection -and vice versa, charge extraction. Having pointed out a possible increase in charge carrier mobility, specifically for the holes as these are transported within the potentially better-ordered domains of the aggregated polymer, hole-only space-charge-limited-current (SCLC) devices were to be investigated for validation.…”
Section: Resultsmentioning
confidence: 78%
“…The EL spectra are depicted in Figure 6 right. Here, the ratio of the single transitions, especially the polymer emission (peaking at ~ 630 nm) and the charge transfer emission (peaking at 920-950 nm), is relevant [65]. A dramatic increase of the charge transfer (CT) emission (around 800 nm to 1100 nm) is observed, compared to the polymer emission (around 560 nm to 730 nm).…”
Section: Resultsmentioning
confidence: 99%